Air polution index (API) real time monitoring system - Ruslan, Norhafizah (2015)
This project is to develop a low cost, mobile Air Pollutant Index (API) Monitoring System, which consists of Sharp GP2Y1010AU0F optical dust detector as a sensor for dust, Arduino Uno and LCD Keypad Shield. A signal conditioner has been used to amplify and extend the range of the sensor reading for a more accurate result. Readings from the sensor has been compared with reference data from the Department of Environment, Malaysia to ensure the results validity of the developed system. The developed dust detector is expected to provide a relatively accurate API reading and suitable to be used for the detection and monitoring of dust concentrations for industrial areas around Parit Raja, Johor.